Analysis of Entrepreneurial Orientation, Market Orientation and Social Media on Competitive Advantage - Try Mustika Murty; R. Deni Muhammad Danial; Dicky Jhoansyah (Dinasti Publisher, 2025)
The study used Entrepreneurial Orientation variables as variable, Market Orientation as variable, Social Media as variable, and Competitive Advantage as variable Y. This study aims to determine the effect of Entrepreneurial Orientation, Market Orientation and Social Media variables on Competitive Advantage in Chicken Noodle MSME players in Sukabumi City. The method used in this study is an associative descriptive method with a quantitative approach. The sample used in this study consisted of 157 members registered at Diskumidag Sukabumi City in 2023, using probability sampling method with simple random sampling type. This study used IBM SPSS Version 25 software as a data analysis tool. The results showed that all hypotheses were accepted, which means there is a positive and significant influence between Entrepreneurial Orientation on Competitive Advantage with a t value of 2.887 > t table 1.658 and a significance value of 0.005 < 0.05, Market Orientation on Competitive Advantage with a t value of 2.034 > t table 1.658 and a significance of 0.004 < 0.05, and between Social Media on Competitive Advantage with a t value of 2.018 > t table 1.658 and a significance value of 0.046 < 0.05. Thus all variables are in very strong criteria.